Effective communication system between building occupants and maintenance management: a study in high rise office building, Klang Valley, Malaysia - Yahya, Mohamad Ridzuan; Ibrahim, Md. Najib (Ontario International Development Agency, 2012)
An effective communication in building management depends on the quality, safety and service of its system between maintenance management and building occupants particularly on the operation and maintenance activities. The crucial issue in building management is to develop communication system between maintenance management and building occupants in order to support value aspect in the building. Study on communication in the maintenance management has generally concentrated on the briefing process and the maintenance process. This research identified three attributes of the existing condition of communication system in maintenance management specifically safety practice, management quality and professionalism in operation and maintenance management. Eleven high rise office buildings in Klang Valley, Malaysia have been randomly selected for the study which involving two groups of respondents. In-house maintenance management personnel (MM) and outsourced contractors/consultants (OS) are in maintenance management group whereas building owners (BO) and tenants (T) as the building occupant group have been unstructured interviewed based on the value aspects of communication factors. The results had shown that unsafe practice, inadequate management and unprofessional maintenance management which effected from miscommunication among them in the whole level tasks. In addition, major issues of maintenance management tools: unavailable building policy, poor management of documents, also weak monitoring toward maintenance activities contributed to the insufficient communication system in maintenance management. The paper concludes that a systematic communication system between maintenance management group and building occupant group does not exist yet in high rise office buildings.